Thirsty Energy - Rodriguez, Diego J. (World Bank, Washington, DC, 2014)
The tradeoffs between energy and water have been gaining international attention in recent years as demand for both resources mount and governments continue to struggle to ensure reliable supply to meet sectoral needs. As almost all energy generation processes require significant amounts of water, and water requires energy for treatment and transport, these two resources are inextricably linked. This relationship is the energy-water nexus. Section one of this paper examines the existing models, literature, and management frameworks on the nexus, as it seeks to determine what gaps exist. Section two describes the water demands of power generation in order to identify potential areas of future uncertainty and delineate areas where integrated energy-water management may improve the reliability of operating power plants and the viability of schemes. Finally, section three describes possible solutions that may alleviate challenges resulting from the link between energy and water by improving energy efficiency and integrating water resources management into energy planning.